2018
DOI: 10.3390/w10070923
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of a Spatially Semi-Distributed Hydrological Model for Watershed Scale Runoff Estimation in Northwest Ethiopia

Abstract: Estimation of runoff is vital forplanning activities in relation to integrated watershed management and flood protection measures. This research was conducted at one of the catchments in Abbay River (upper Blue Nile River) basin to assess the applicabilityof the Hydrologic Engineering Centre Hydrological Modelling Software (HEC-HMS) modelfor simulation of runoff. It was aimed at selecting the best loss and transform methods in the model, as well as testing the applicability of the calibrated model to ungauged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…It was found that the curve number, initial abstraction, and lag time were more sensitive, less sensitive and insensitive parameters of the model, respectively. Nearly a similar result was obtained for the peak flow by Zelelew and Melesse [10] which ranges from 37.5 to 60.2%, with a mean value of 50.1% for a model set containing the SCS loss method with Clark's unit hydrograph transform method combination.…”
Section: Eventssupporting
confidence: 69%
See 1 more Smart Citation
“…It was found that the curve number, initial abstraction, and lag time were more sensitive, less sensitive and insensitive parameters of the model, respectively. Nearly a similar result was obtained for the peak flow by Zelelew and Melesse [10] which ranges from 37.5 to 60.2%, with a mean value of 50.1% for a model set containing the SCS loss method with Clark's unit hydrograph transform method combination.…”
Section: Eventssupporting
confidence: 69%
“…In this study, the sensitivity analysis was performed by changing the parameter values in the range of ±25% with 5% intervals. Zelelew and Melesse [10] and Majidi and Shahedi [38] conduct a sensitivity analysis by changing the parameter values in the range of ±30% with 5% intervals until the best fit between the observed and simulated parameters in the given hydrograph was obtained. Another study by Sardoii et al [13] used a parameter change of ±15% with a 5% interval in order to analyze the sensitivity of the calibration parameters in the Amirkabir Dam Watershed in Iran.…”
Section: Model Calibration and Validationmentioning
confidence: 99%
“…Many diverse criteria are used to assess the performance efficiency of hydrological models [61]. Based on the literature [27,62,63] the following were used to compare the performance of the flow model in relation to the observed flows: NSE-broadly used for calibration and validation of hydrological models regarding discharge, r-primarily used for evaluation of the timing of simulated and observed time series, PBias-used to investigate the tendency of over-or underestimation of simulated flow, and rPFD-important criterion in terms of flood risk.…”
Section: Calibration and Validationmentioning
confidence: 99%
“…Therefore, a complete understanding of comparative model performance requires applications under different hydrologic conditions and watershed scales. As reported by [6], SWAT has been successfully applied to simulate streamflow in different basins of the country Ethiopia and HEC-HEM has been also successfully applied for hydrological studies in different Ethiopian basins [14]. Therefore, the objective of the present study is to compare and assess the suitability of those two widely-used watershed simulation models, namely HEC-HMS and SWAT, for simulating the hydrology of a Katar River Basin, the Central Rift Valley (CRV) Lake Basin of Ethiopia.…”
Section: Introductionmentioning
confidence: 96%